2007
DOI: 10.1534/genetics.107.074963
|View full text |Cite
|
Sign up to set email alerts
|

The Reacquisition of Biotin Prototrophy in Saccharomyces cerevisiae Involved Horizontal Gene Transfer, Gene Duplication and Gene Clustering

Abstract: The synthesis of biotin, a vitamin required for many carboxylation reactions, is a variable trait in Saccharomyces cerevisiae. Many S. cerevisiae strains, including common laboratory strains, contain only a partial biotin synthesis pathway. We here report the identification of the first step necessary for the biotin synthesis pathway in S. cerevisiae. The biotin auxotroph strain S288c was able to grow on media lacking biotin when BIO1 and the known biotin synthesis gene BIO6 were introduced together on a plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
131
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 55 publications
2
131
1
2
Order By: Relevance
“…Some of these genes, like SNO/SNZ and SAM, are functionally clustered. Previous studies have shown that there are very few functionally clustered genes in S. cerevisiae, and that those that are clustered tend to be associated with specific functions that differ between strains (Hall and Dietrich 2007). Analogous distributions of nonessential genes are also found in other species.…”
Section: Discussionmentioning
confidence: 85%
“…Some of these genes, like SNO/SNZ and SAM, are functionally clustered. Previous studies have shown that there are very few functionally clustered genes in S. cerevisiae, and that those that are clustered tend to be associated with specific functions that differ between strains (Hall and Dietrich 2007). Analogous distributions of nonessential genes are also found in other species.…”
Section: Discussionmentioning
confidence: 85%
“…Although no structural ortholog of bioF is found in S. cerevisiae, AON synthase is encoded in this organism and in closely related species by BIO6, a structural paralog of the BIO3 gene, which encodes the bacterium-type DAN synthase (12,30). Because no peroxisomal targeting sequence was identified in Bio6p, we investigated the roles of the peroxisome and ␤-oxidation cycle in S. cerevisiae biotin synthesis.…”
Section: Biotin Synthesis Requiresmentioning
confidence: 99%
“…Because no peroxisomal targeting sequence was identified in Bio6p, we investigated the roles of the peroxisome and ␤-oxidation cycle in S. cerevisiae biotin synthesis. Many S. cerevisiae laboratory strains, including reference strain BY4742 used in the Saccharomyces Genome Deletion Project, require biotin due the absence of the syntenic BIO6 and BIO1 genes (12,30). The BIO6-BIO1 gene cluster of prototrophic strain A364a was cloned and introduced into BY4742 and the deletions mutants derived from it, and all strains were tested for biotin prototrophy.…”
Section: Biotin Synthesis Requiresmentioning
confidence: 99%
“…However, eukaryotic gene order is not as random as it first appeared, and clusters of functionally related but nonhomologous genes now have been identified in the genomes of animals and fungi (2,3). These clusters include the MHC locus in mammals (4), gene clusters for nutrient use in yeast (5)(6)(7), and numerous clusters for diverse secondary metabolic pathways in filamentous fungi (8,9). Although the genes within these eukaryotic clusters are transcribed independently, these clusters have certain operon-like features (physical clustering and coregulation) (3).…”
mentioning
confidence: 99%